The result of physical fitness learning in sman 36 jakarta during the covid-19 pandemic - M. Yudistira Arief; Ramdan Pelana; Iman Sulaiman (Gladi : Jurnal Ilmu Keolahragaan, 2022)
Inappropriate learning methods and low learning motivation of students will have an impact on physical fitness learning outcomes. The purpose of this study was to obtain a more complete picture of the influence of learning methods and learning motivation on Physical Education Learning Outcomes.The research method is an experiment with a treatment by level 2x2 design. The research sample is 160 students of class XII. Hypothesis testing using the Tukey test. Based on the results of the study, it can be concluded: 1) there is a significant difference in the effect between methods A1 and A2 on Y. This is evidenced by the value of Fcount = 20.20 > Ftable = 3.90. 2) There is a significant interaction effect between A and B on Y. The results are significant, because Fcount = 84.64 > Ftable = 3.90. 3) there is a significant difference in Y using A1 and A2 in group B1. This is evidenced by the value of Qcount = 12.78 > Qtable = 3.79. 4) there is a significant difference in Y results using the A1 and A2 learning methods in group B2. It is proven by the value of Qcount = 3.98 > Qtable = 3.79.